Assessing the role of FecB mutation in productivity of Indian sheep - Pardeshi, V. C.; Sainani, Mohini N.; Maddox, J. F.; Ghalsasi, P. M.; Nimbkar, C.; Gupta, V. S. (Current Science, 2005)
DNA samples from four Indian sheep breeds, viz. Garole, Deccani, Bannur and Madras Red were screened by PCR-RFLP to determine the presence of FecB mutation in these breeds. The Garole was the only breed, which carried the FecB mutation. The FecB mutation was introgressed from Garole sheep into Deccani sheep and Bannur sheep, and the performance of the crossbred sheep is being monitored in subsequent generations. Approximately half of the first backcross ewes (progeny of FecB heterozygote F1 rams) was found to carry one copy of FecB mutation, as expected. The FecB PCR-RFLP test was found to be fast, accurate and useful as a tool for making breeding decisions.
Keywords: FecB (Booroola) gene; Garole sheep; PCR-RFLP test; prolificacy

Mitochondrial haplotypes reveal a strong genetic structure for three Indian sheep breeds - Pardeshi, V. C.; Kadoo, Narendra Y.; Sainani, Mohini N.; Meadows, J. R. S.; Kijas, J. W.; Gupta, Vidya S. (Animal Genetics, 2007)
This survey represents the first characterization of mitochondrial DNA diversity within three breeds of Indian sheep (two strains of the Deccani breed, as well as the Bannur and Garole breeds) from different geographic regions and with divergent phenotypic characteristics. A 1061-bp fragment of the mitochondrial genome spanning the control region, a portion of the 12S rRNA gene and the complete phenyl tRNA gene, was sequenced from 73 animals and compared with the corresponding published sequence from European and Asian breeds and the European Mouflon (Ovis musimon). Analysis of all 156 sequences revealed 73 haplotypes, 52 of which belonged to the Indian breeds. The three Indian breeds had no haplotypes in common, but one Indian haplotype was shared with European and other Asian breeds. The highest nucleotide and haplotype diversity was observed in the Bannur breed (0.00355 and 0.981 respectively), while the minimum was in the Sangamneri strain of the Deccani breed (0.00167 and 0.882 respectively). All 52 Indian haplotypes belonged to mitochondrial lineage A. Therefore, these Indian sheep are distinct from other Asian and European breeds studied so far. The relationships among the haplotypes showed strong breed structure and almost no introgression among these Indian breeds, consistent with Indian sheep husbandry, which discourages genetic exchange between breeds. These results have implications for the conservation of India's ovine biodiversity and suggest a common origin for the breeds investigated.
Keywords: Genetic diversity; Indian sheep; mitochondrial DNA; mitochondrial lineage; phylogeographic distribution; sheep domestication